(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
As representatives of the national revival in Turkestan, the enlighteners defended the interests of the people. Through their works and articles, they called the people to enlightenment. Mufti Mahmudkhodja Behbudiy guided them on this path.